2001
DOI: 10.1007/s101620010045
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical Estimates of Cochlear Phase Response: Masking by Harmonic Complexes

Abstract: In some cases, small modifications to the gammachirp filter produced better quantitative predictions of curvature changes across frequency, but this filter, as Harmonic complexes with identical component frequencies and amplitudes but different phase spectra implemented here, was unable to accurately represent all the data. may be differentially effective as maskers. Such harmonic waveforms, constructed with positive or negaKeywords: masking, phase, auditory filters, harmonic complexes tive Schroeder phases, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 11 publications
(1 reference statement)
2
48
2
Order By: Relevance
“…The large differences in masking by +SCHR and −SCHR have been explained as a hypothesized interaction between the phase characteristic of the basilar membrane and the phase spectrum of the +SCHR waveform that produces an internally peaky within-channel waveform (Kohlrausch and Sander 1995;Leek and Lentz 2001;Oxenham and Dau 2001). This internal transformation of the +SCHR waveform might produce an additional cue to aid the discrimination tested here as long as the F0 is low enough.…”
Section: Discrimination Of Schroeder-phase Harmonic Complexesmentioning
confidence: 88%
See 1 more Smart Citation
“…The large differences in masking by +SCHR and −SCHR have been explained as a hypothesized interaction between the phase characteristic of the basilar membrane and the phase spectrum of the +SCHR waveform that produces an internally peaky within-channel waveform (Kohlrausch and Sander 1995;Leek and Lentz 2001;Oxenham and Dau 2001). This internal transformation of the +SCHR waveform might produce an additional cue to aid the discrimination tested here as long as the F0 is low enough.…”
Section: Discrimination Of Schroeder-phase Harmonic Complexesmentioning
confidence: 88%
“…Several studies have demonstrated differences in the masking effectiveness of positive-(+SCHR) and negative-phase (−SCHR) versions of Schroeder harmonic complexes in normal-hearing (NH) and hearingimpaired (HI) listeners (Carlyon and Datta 1997;Kohlrausch and Sander 1995;Lauer et al 2006;Leek et al 2000;Lentz and Leek 2001;Dau 2001, 2004;Smith et al 1986;Summers and Leek 1998). These complexes have similar envelopes and long-term frequency spectra but reversed withinperiod temporal structure.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed above, the phase effect was calculated as the difference between the maximum and minimum masked thresholds in the Schroeder-phase masking function. The magnitude of the phase effect is related to the nonlinearity of cochlear function, with larger phase effects being observed in normal and healthy cochleae and reduced phase effects being observed in people with sensorineural hearing loss (Gifford et al, 2008;Kohlrausch & Sander, 1995;Lentz & Leek, 2001;Oxenham & Dau, 2004;Summers, 2000).…”
Section: Output Measures Obtained From the Schroeder-phase Masking Testmentioning
confidence: 99%
“…Schroeder-phase harmonic complexes (Schroeder, 1970) have been used in many psychophysical experiments to examine the phase curvature of the auditory filter at characteristic frequencies, as well as other aspects of cochlear nonlinearity (Gifford et al, 2008;Kohlrausch & Sander, 1995;Lentz & Leek, 2001;Recio & Rhode, 2000;Summers & Leek, 1998). These complexes, which have identical amplitude spectra but which differ in their phase spectra (see Figure 1), have been observed to stimulate different patterns of basilar membrane excitation (Recio & Rhode, uniform output over time, which makes them more effective maskers and results in higher masked thresholds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation